Design of microstrip patch antenna using slotted partial ground and addition of stairs and stubs for UWB application - Islam, Md Rafiqul; Alam, A H M Zahirul; J Khan, M Feroze Akbar; Alkaraki, Shaker (Cyber Journals, 2012)
This paper presents the design with optimum geometry of a novel UWB rectangular patch antenna. A simple narrowband patch antenna is designed before proceeding to the geometry of UWB antenna. A special configuration of patch antenna with slotted partial ground and addition of stairs and stubs was designed and optimized using CST Microwave Studio (CSTMWS). The designed antenna was fabricated, tested and compared with the simulation results. The proposed antenna’s characteristics were investigated with various options and found to operate satisfactorily. A remarkable improvement has been noticed in this design. Moreover, the antennas structure offers great advantages due to its simple designs and small dimensions.